Effect of defense holes in isotropic homogeneous plate - Lim, Chu Wei. (2011)
Boundary Element Method was used in analyzing the reduction of stress concentration on an isotopic homogeneous plate with a central circular hole by using defense holes. Defense holes were placed in the direction of loading and in the direction perpendicular to the loading to investigate the stress reduction around a circular hole. By varying the defense holes distance from the central main hole and the size of the defense hole, it was noticed that the stress concentration is reduced when the defense holes are further away from the central hole and significant stress reduction was observed when the size of the defense holes are at least half the size of the central main hole.